Analisis Kebutuhan Fisik Tim Sepakbola Putra Gresik pada Porprov VII Jawa Timur Tahun 2022 - M. Adib Laswar Irkhami; Made Pramono (Pendekar : Jurnal Pendidikan Berkarakter, 2024)
Football is a team sport where each team consists of 11 players who play according to the techniques and tactics according to the position of the game, in one team consisting of goalkeepers, defenders, midfielders and attackers. The most influential factor in achieving success in football is the physical factor, where physical condition is the most important component to support achievement. At the implementation of the provincial sports week in Jember in 2022, the Gresik contingent in the men's football sport failed to bring home a medal, the Gresik men's football contingent failed in the pre-Provin event ranked in the lower class in Group G by collecting points 1. The purpose of this research is to knowing the physical condition of the Gresik contingent in the men's soccer sport in the Porprov VII event. The hamstring muscle strength test was carried out using the Nordic hamstring test while the abdominal and arm muscle strength tests were carried out using the abdominal roller test item, the agility test was carried out using the 30 meter sprint test, the explosive power test was carried out using the rope jump test item, the agility test was carried out using the Z test, and the endurance test was carried out using the Multistage Fitness Test. Data analysis showed that the ability of speed, agility and endurance ability of the Gresik VII Porprov Contingent men's soccer athletes were included in the "good" category. While the strength in the abdominal muscles is included in the "Less" category and Hamstring muscle strength is included in the "Very Less" category. And the explosive power capability is included in the "medium" category.